Motivasi Orang Tua Menitipkan Anaknya di Daycare - Sesilia Monika (Fakultas Psikologi Universitas Tarumanagara, 2014)
Daycare becomes an alternative solution for parents who want to leave their children while they work. With its existing programs, parents believe that their children are given sufficient stimulation in daycare. Moreover, parents also believe that in the daycare their children could be more secure, because daycare is generally set up near the office area, so parents can monitor the daily activities of children at any time. The method used in this research is a qualitative descriptive method. From the results of this research, it was found that the main reason parents leave their children in daycare is because of the safety factor. Seventh subjects in this study did not have a trusted person which can help them keep an eye on the child every day. Thus, they leave their children in daycare with the consideration that in daycare facilities are equipped with CCTV. Thus, parents can see directly through the internet if they want to know the activities of the child at the time. In addition, parents hope that daycare had programs that can fulfill the language development, communication, cognitive, affective, and socioemotional aspects of the children. Parents also hope that daycare can meet the nutritional intake of children according to age, so that the child can be fulfilled also biological needs.Keywords: daycare, parents’ motivation